Revisiting the occurrence and evidence of endodermis in angiosperm shoots - Seago, James L. (Flora. Morphologie, Geobotanik, Oekophysiologie, 2020)
•The subject of this research is the occurrence and evidence of endodermis and its Casparian bands in the shoots, primarily stems, in the angiosperms.•The demonstrations of the Casparian bands have gone far beyond what other researchers have done.•The evidence produced in photographs should contribute to the understanding of angiosperm anatomy and phylogeny. A sampling of angiosperms across a broad spectrum of families and generas was done to determine if angiosperms from the ANA grade basal angiosperms to the Zingiberales of the monocots and Apiales of the eudicots had an endodermis with demonstrable Casparian bands in shoots because the literature has a paucity of demonstrable images, especially for key basal plants. In the Amborellales, Amborella had no stem endodermis, but the aquatic Trithuria of the Nymphaeales had a monostele in which a layer endodermis enclosed its stem axial vascular tissues. Cabomba, Brasenia, and Nuphar of the Nymphaeales had polysteles in which an endodermis of distinct Casparian bands encircled each axial vascular bundle; Nymphaea had either an atactostele or a reduced polystele with only a few axial vascular bundles surrounded by endodermis. Among the magnoliids, Saururus and Houttuynia had monosteles with distinct endodermis Casparian bands. In many monocots, from Acorus, Acorales, to Thalia, Zingiberales, there was a monostele with an endodermis of Casparian bands surrounding a central cylinder of scattered axial vascular bundles. At the base of the eudicots, Ceratophyllum had a vascular core without endodermis. Some members of the Ranunuculales had stem endodermis in a polystelic arrangement. Nelumbo, Proteales, had a monostele of Casparian bands only in stolons. Unusual endodermal and vascular patterns, siphonosteles, were found in Gunnera, Gunnerales. Most eudicots with stem endodermis usually had a monostele or one endodermal layer of Casparian bands only surrounding one ring of vascular bundles, e. g., Myriophyllum, Drosera, Hippuris, Alternanthera, Lysimachia, and Hydrocotyle, but a polystele was present in Justicia. Some leaf petioles and lamina, e. g., Gunnera, Myriophyllum, Hippuris, and Hydrocotyle, had endodermis around their individual vascular bundles. While a stem endodermis was a distinct feature of aquatic or wetland plants, derived from terrestrial ancestors, the presence of stem endodermis by plants at the bases of some major angiosperm lines suggests that it may have been present early in angiosperm evolution.